Differential Cellular Tropism of Lentivirus and Adeno-Associated Virus in the Brain of Cynomolgus Monkey (vol 25, pg 48, 2016) - An, Heeyoung; Cho, Doo-Wan; Lee, Seung Eun; Yang, Young-Su; Han, Su-Cheol; Lee, C. Justin (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2021)
<Correction> Heeyoung An1,2, Doo-Wan Cho3, Seung Eun Lee2,Young-Su Yang3, Su-Cheol Han3* and C. Justin Lee1,2* 1KU-KIST Graduate School of Converging Science and Technology, Korea University, Seoul 02841, 2Center for Neuroscience and Functional Connectomics, Brain Science Institute, Korea Institute of Science and Technology (KIST), Seoul 02792, 3General Toxicology Research Center, Jeonbuk Department of Inhalation Research, Korea Institute of Toxicology, KRICT, Jeongeup 56212, Korea. ？ Experimental Neurobiology 2021.